IgA vasculitis update: Epidemiology, pathogenesis, and biomarkers - Xu, Liyun; Li, Yongzhen; Wu, Xiaochuan (Frontiers in Immunology, 2022)
Immunoglobulin A vasculitis (IgAV), formerly known as Henoch-Schonlein purpura, is the most common systemic vasculitis in children, characterized by diverse clinical manifestations with a wide spectrum ranging from isolated cutaneous vasculitis to systemic involvement. The incidence of IgAV is geographically and ethnically variable, with a prevalence in autumn and winter, suggesting a driven role that genetic and environmental factors plays in the disease. Although IgAV has a certain degree of natural remission, it varies widely among individuals, some patients can suffer from severe renal involvement and even progress to end-stage renal disease. Its pathogenesis is complex and has not been fully elucidated. The formations of galactose-deficient IgA1 (Gd-IgA1) and related immune complexes play a vital role in promoting the occurrence and development of IgAV nephritis, in addition, neutrophil activation is stimulated through the binding of IgA to Fc alpha receptor I expressed on its surface, resulting in systemic vascular inflammation and tissue damage. Starting from the epidemiological characteristics, this article will review the role of immunological factors such as Gd-IgA1, autoantibodies, circulating immune complexes, complement system, cellular immunization, and the contributions of environmental and genetic factors in the pathogenesis of IgAV, and conclude the major biomarkers for IgAV.